1995
DOI: 10.1111/j.1365-2249.1995.tb03798.x
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for lysozyme in determining acute exacerbation in chronic bronchitis

Abstract: SUMMARYThe aggregation of non-serotypable Haemophilus influenzae (NTHI) by whole saliva from patients with chronic obstructive lung disease (COLD) was investigated. Significant differences were observed between salivary aggregating activity of a control and COLD population (/* < 0 001). Saliva from patients less prone to acute exacerbations had a greater capacity to aggregate bacteria compared with saliva from patients with a predilection to infection. The mechanism of salivamediated aggregation of NTHI was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…Salivary dysfunction may predispose to oral colonization and subsequent recurrent pulmonary infections (23). Furthermore, sicca symptoms have been reported in association with pulmonary involvement in cGVHD (3).…”
Section: Resultsmentioning
confidence: 99%
“…Salivary dysfunction may predispose to oral colonization and subsequent recurrent pulmonary infections (23). Furthermore, sicca symptoms have been reported in association with pulmonary involvement in cGVHD (3).…”
Section: Resultsmentioning
confidence: 99%
“…Although little is known of the role of EAMs in COPD (8)(9)(10), their antibacterial, and more recently, antiviral activities have been established (11). Their potential importance in COPD is underscored by the finding that low levels of two EAMs (secretory leukoprotease inhibitor [SLPI] and lysozyme) are associated with increased frequency of COPD exacerbations and a decreased ability to aggregate NTHI (12,13). In addition, data are emerging showing that EAMs such as defensins and LL-37 can be chemotactic for DCs and can contribute to their maturation program (14)(15)(16).…”
mentioning
confidence: 99%
“…There is also evidence to suggest that this therapeutic approach stimulates a Th1 type response against chronic microbial infections 49. Recently it was demonstrated that NTHi oral immunotherapy prevented NTHi from penetrating into the terminal airways,15 and this was correlated with an enhanced circulating specific antigen reactive T cell response and a reduction in the level of salivary lysozyme,50 a marker of luminal inflammation in COPD 51. Prospective therapeutic studies aimed at reducing the intrabronchial load of NTHi, which correlate improvement of bronchial hyperreactivity and clinical bronchospasm with laboratory parameters of IgE-mediated hypersensitivity, are needed to determine more clearly the clinical relevance of specific IgE antibody in subjects with mild and severe COPD.…”
Section: Discussionmentioning
confidence: 99%